2017
DOI: 10.3847/2041-8213/836/1/l14
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Hard Ionizing Spectrum from a z = 6.11 Stellar Population

Abstract: We present the Magellan/FIRE detection of highly ionized C IVλ1550 and O III]λ1666 in a deep infrared spectrum of the z=6.11 gravitationally lensed low-mass galaxy RXC J2248.7-4431-ID3, which has previously known Lyα. No corresponding emission is detected at the expected location of He IIλ1640. The upper limit on He II, paired with detection of O III] and C IV, constrains possible ionization scenarios. Production of C IV and O III] requires ionizing photons of 2.5-3.5 Ryd, but once in that state their multip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
226
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(258 citation statements)
references
References 49 publications
27
226
5
Order By: Relevance
“…The detection of nebular high-ionization emission lines has underscored the considerable contribution of hot and massive stars to the transparency of the medium in low-luminosity (L L*  ) systems (Vanzella et al 2016a), as expected in scenarios in which stellar winds and supernova explosions blow cavities in the interstellar medium (e.g., Jaskot & Oey 2013;Micheva et al 2017). In fact, the rest-frame ultraviolet and optical line ratios observed in z 0  , z 2 3 = -and z 6 > galaxies suggest a possible evolution of the ionizing radiation field, such that the presence of hot stars seems more common at high redshift, with blackbody mean effective temperatures on the order of 50.000-60.000 K at z 2 3 = - (Fosbury et al 2003;Steidel et al 2014;Holden et al 2016), or even hotter at z 6 > (Stark et al 2015;Mainali et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…The detection of nebular high-ionization emission lines has underscored the considerable contribution of hot and massive stars to the transparency of the medium in low-luminosity (L L*  ) systems (Vanzella et al 2016a), as expected in scenarios in which stellar winds and supernova explosions blow cavities in the interstellar medium (e.g., Jaskot & Oey 2013;Micheva et al 2017). In fact, the rest-frame ultraviolet and optical line ratios observed in z 0  , z 2 3 = -and z 6 > galaxies suggest a possible evolution of the ionizing radiation field, such that the presence of hot stars seems more common at high redshift, with blackbody mean effective temperatures on the order of 50.000-60.000 K at z 2 3 = - (Fosbury et al 2003;Steidel et al 2014;Holden et al 2016), or even hotter at z 6 > (Stark et al 2015;Mainali et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…We will specifically address the first question in a companion paper, but in this study, we start by comparing galaxy and AGN emission in the UV, and we specifically focus on two energies, 54.4 eV and 47.9 eV (228 and 258 Å). Photons with these energies or higher are required to produce the He II and C IV lines that are now observed in high-z galaxy spectra (Stark et al 2015a(Stark et al , 2015bMainali et al 2017). In Figure 10 we calculate the median of the ratio of the monochromatic luminosity produced by the AGN and produced by the galaxy stellar population as a function of the BH mass.…”
Section: Galaxy Versus Agn: Uv Radiation Powering Emission Linesmentioning
confidence: 99%
“…In particular, Mainali et al (2017) showed that UV line ratios can be used to distinguish between AGNs and massive hot metal-poor stars as a powering mechanism using dedicated emission line models (Feltre et al 2016). Mainali et al (2017) argued that based on the presence of C IV and lack of He II, this source was likely to have a break in the ionizing spectrum between 47.9 and 54.4 eV, consistent with a stellar ionizing spectrum and inconsistent with an AGN power-law spectrum. The fact that they detect strong O III] provided further evidence in favor of metal-poor hot stars, as an AGN spectrum would likely have weaker O III] given that oxygen is triply ionized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations